Upaya Peningkatan Kompetensi Karyawan Untuk Mendorong Efektivitas Kinerja Pada Koperasi Bangun Kemandirian Bangsa, Pancoran, Jakarta Selatan - Bambang Setiawan; Joned Ceilendra Saksana; T Ramli Zakaria (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2023)
Human resource management aims to improve the effectiveness of human resources in the organization is very important. For this reason, the Cooperative Builds National Independence seeks to improve the competence of its employees through education and training activities in encouraging performance effectiveness. The purpose of the study is to determine the performance of employees of the Bangun Kemandirian Bangsa Cooperative, to determine the implementation of education and training activities at the Bangun Kemandirian Bangsa Cooperative in an effort to improve the competence of its employees and to know the development of employee performance before and after participating in education and training programs. This study used qualitative research methods with data collection techniques using interviews, observation and documentation. In this study, the informants selected were 6 employees of the Cooperative Build National Independence. The results of the study concluded that the performance of the employees of the Koperasi Bangun Kemandirian Bangsa was quite good as seen from the ability to carry out and complete their work, although it still had to be improved. The implementation of education and training programs in an effort to improve employee competence has been carried out well and has a positive impact on the effectiveness of employee performance of the Koperasi Bangun Kemaditrian Bangsa